2016
DOI: 10.1002/cctc.201501415
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Fiber‐Structured Pd–Au–CuOx: Preparation and Catalytic Performance in the Vapor‐Phase Hydrogenation of Dimethyl Oxalate to Ethylene Glycol

Abstract: Cu‐fiber‐structured ternary Pd–Au–CuOx catalysts engineered from nano‐ to macro‐scales have been developed for the vapor‐phase dimethyl oxalate (DMO) hydrogenation to ethylene glycol (EG), with the aid of galvanic deposition of Pd and Au onto a thin‐sheet microfibrous structure using 8 μm Cu fiber. Effects of Pd and Au loadings and their ratio have been investigated on the catalyst performance as well as the reaction conditions including reaction temperature and pressure, liquid weight hourly space velocity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Han et al. reported Pd‐Au‐CuO x prepared through the galvanic deposition of Pd and Au onto a thin‐sheet, microfibrous structure by using 8 mm Cu fibers, which synergistically promoted the hydrogenation activity and stabilized the Cu + sites . Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al. reported Pd‐Au‐CuO x prepared through the galvanic deposition of Pd and Au onto a thin‐sheet, microfibrous structure by using 8 mm Cu fibers, which synergistically promoted the hydrogenation activity and stabilized the Cu + sites . Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al reported Pd-Au-CuO x prepared through the galvanic deposition of Pd and Au onto at hin-sheet, microfibrous structure by using 8mmC uf ibers, which synergistically promoted the hydrogenation activity and stabilized the Cu + sites. [7] Zhang et al reported ap lasma-treated Cu-Ni/ZrO 2 catalyst that had enhanced Cu dispersion. [4] Silica-supported copperc atalysts have excellent performance and have widely been used in hydrogenation reactions because of their excellent performance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that Al 2 O 3 support has been used for widespread applications, the relatively high quantity of acid sites on Al 2 O 3 surface may catalyze unwanted isomerization or oligomerization reactions according to many studies ,,,. Therefore, in the present study, an inert SiO 2 support with a large surface was considered as a suitable choice ,…”
Section: Introductionmentioning
confidence: 99%
“…It is generally thought that Cu dispersion and/or the distribution of Cu 0 and Cu + species have great influence on the product selectivity during the hydrogenation process over Cu‐based catalysts . Tuning catalyst preparation parameters (e. g. promoters, Cu loading, calcination temperature) of Cu‐based catalysts is really efficient to modify Cu dispersion and Cu + /(Cu 0 +Cu + ) value. According to the previous literatures, it is plausible that both more dispersed Cu species and higher Cu + /(Cu 0 +Cu + ) value are effective to improve the product selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation